Budaya Organisasi dan Kinerja pada Perawat di Rumah Sakit - Simarmata, Nicholas; K. Hedo, Dian Jayantari Putri (Universitas Muhammadiyah Metro, 2025)
The contribution of professional nurses in hospital is an important provision for the sustainability of hospital organizations. However, there are challenges for the hospital organizations, namely low nurses’ performances due to the implementation of inappropriate organizational culture. This study aimed to examine the relationship between organizational culture and nurse performance in hospitals. This study was a quantitative correlational study. The population was nurses in hospitals in Indonesia with a sample of 619 nurses who met the criteria of male or female gender, minimum education equivalent to high school, and working for at least 1 year. The sampling method was convenience non-probability sampling, data was collected with organizational culture scale and performance scale and was analyzed with simple linear regression. The study results stated that there was relationship between organizational culture and nurse performance in hospitals with correlation value of 0.347 and probability value below 0.05. The implementation of flexible and responsive hospital organizational culture is a crucial factor in producing a positive impact on nurses’ performances in hospitals.